Redefining resilience: The case of small entrepreneurs in Saudi Arabia - Alshebami, Ali Saleh (Frontiers in Environmental Science, 2023)
The survival of enterprises and the effective management of daily problems and obstacles, particularly those faced by small entrepreneurs, depend heavily on resilience. This study examines the critical elements that help small Saudi entrepreneurs strengthen their entrepreneurial resilience through internal locus of control and entrepreneurial self-efficacy, particularly during trying times. The partial least squares structural equation modeling (PLS–SEM) technique was used to analyse the responses of 207 small entrepreneurs operating in various regions of Saudi Arabia. The convenience sampling technique was used, and the data was collected using an online questionnaire. The study found a strong relationship between entrepreneurial resilience, internal locus of control, and entrepreneurial self-efficacy. These results demonstrated that entrepreneurial self-efficacy could mediate the relationship between the internal locus of control and entrepreneurial resilience. Finally, the study addressed limitations and provided recommendations for policymakers and potential authors.